Properties, characteristics and applications of microbubbles for sonothrombolysis. - de Saint Victor, M; Crake, C; Coussios, C; Stride, E (2014)
INTRODUCTION: Ultrasound enhancement of thrombolysis (sonothrombolysis) is further potentiated by administration of acoustically active microbubbles, which may be developed into powerful adjuvant therapies for thrombolytic treatment of occlusive conditions such as ischaemic stroke. AREAS COVERED: The role of microbubbles in sonothrombolysis is evaluated based on published in vitro and in vivo evidence and a critical review of clinical trials to date. Microbubble, ultrasound and drug parameters compiled from a broad search of the existing literature are tabulated. Mechanisms of microbubble-enhanced sonothrombolysis are discussed, with particular focus on acoustic cavitation and thermal effects. A number of challenges to widespread clinical adoption are identified. Key factors for future optimisation of treatment and microbubble design are proposed. EXPERT OPINION: Microbubble enhancement of thrombolysis is supported by a broad range of in vitro and in vivo evidence that demonstrates improved lysis compared to conventional drug treatment or ultrasound without microbubbles. Clinically, this is shown by accelerated recanalisation of occluded arteries; however, further research is needed to ensure patient safety. Before such techniques can enter widespread clinical practice, an improved understanding of the role of microbubbles in sonothrombolysis is required, in addition to demonstration of significant improvement over existing treatments and the development of reliable real-time monitoring protocols.